Condensation derivatives of 4-isopropylbenzaldehyde with acetophenone from the red alga Laurencia tristicha. (December 2021) - Zhang, Juan; Shi, Lun-Yong; Ding, Lan-Ping; Liu, Yang; Liang, Hong; Tu, Peng-Fei; Li, Li; Zhang, Qing-Ying
Abstract: Seven undescribed condensation derivatives of 4-isopropylbenzaldehyde with acetophenone, including one 1, 3, 5-trisubstituted pentane-1, 5-dione, two 1, 3, 4, 5, 7-pentasubstituted heptane-1, 7-diones and four 1, 2, 3, 4, 5-pentasubstituted cyclohexanols, together with two known flavonoids, were obtained from the red alga Laurencia tristicha . The relative configurations were elucidated by extensive spectroscopic data analysis of MS, 1D and 2D NMR, while the absolute configurations were determined by comparing the experimental and calculated electronic circular dichroism spectra. All the isolates were proven to be naturally occurring in the red alga by LC-MS analysis, and these 1, 3, 5-trisubstituted-pentane-1, 5-dione, 1, 3, 4, 5, 7-pentasubstituted-heptane-1, 7-diones and 1, 2, 3, 4, 5-pentasubstituted-cyclohexanols were reported from natural sources for the first time. The proposed biogenetic pathway of the isolates was also discussed. Graphical abstract: Seven undescribed condensation derivatives of 4-isopropylbenzaldehyde with acetophenone, together with two known flavonoids, were obtained from the red alga Laurencia tristicha . Image 1 Highlights: Seven condensation derivatives of 4-isopropylbenzaldehyde with acetophenone were obtained from the red alga Laurencia tristicha. The seven condensation derivatives were undescribed and firstly reported from natural sources. The seven condensation derivatives and co-isolated two known flavonoids were proven to be naturally occurring in the red alga.